THE EFFECT OF FLAT COVERS ON THE QUANTITY AND QUALITY OF ARUGULA YIELD - Anna Francke (Acta Scientiarum Polonorum: Hortorum Cultus, 2011)
Arugula is a common name for several leafy vegetable species of the family Brassicaceae. Eruca sativa and Diplotaxis tenuifolia are grown commercially for human consumption. The effect of two types of flat covers, perforated PE film and non-woven PP fabric, on the yield and quality of arugula was determined in the study. A two-factorial experiment was conducted in 2006–2008 in the Experimental Garden of the University of Warmia and Mazury in Olsztyn. The first experimental factor was plant species – Diplotaxis tenuifolia and Eruca sativa. The second factor was the type of plant cover – perforated PE film with 100 openings per m2 and non-woven PP fabric with surface density of 17 g·m-2. Plants grown without protective cover served as control. Arugula was grown on proper black earth soil of quality class IIIb and cereal-fodder strong complex. Each year, seeds were sown in the middle of April. After planting out in the field, the seedlings were covered with PE film and non-woven PP fabric. The covers were removed after approximately five weeks. Leaves were harvested gradually over the growing season, one to three times from each treatment. The use of PE film and non-woven PP fabric covers had a significant effect on the total and marketable yield of arugula leaves. In 2006–2008, the highest average total yield was obtained from plots covered with perforated PE film. The marketable yield had a higher share of the total yield in Diplotaxis tenuifolia and in plots covered with perforated PE film, compared with control plots and plots covered with nonwoven PP fabric. The rosettes of Diplotaxis tenuifolia consisted of a higher number of leaves, while Eruca sativa had longer leaves and higher rosette biomass.